EMPOWERING BOGOR COFFEE FARMS THROUGH THE COFFEE FUN TRIP EDUTAINMENT PROGRAM - Hakim, Nurman; Kartika, Tika; Hidayat, Muhammad Faisal (LPPM Univ. Ibn Khaldun Bogor, 2025)
The green economy significantly impacts Indonesia's economy, with agriculture, forestry, and fisheries contributing 13.70% of the GDP in 2020 and 13.28% in 2021. Coffee, as a major agricultural commodity, serves as a vital non-oil export and has a strong domestic market presence, placing Indonesia as the fifth-largest coffee-consuming country worldwide. This paper highlights the innovative potential of edutainment tourism, focusing on the Coffee Fun Trip initiative in Bogor as a sustainable method to empower local coffee farmers. The Coffee Fun Trip blends educational and recreational experiences, enabling visitors to connect with the coffee production process while exploring scenic plantations and local cultural heritage. Initial efforts involve preparing accessible coffee plantations with infrastructure like camping grounds, pathways, and roasting equipment. Activities such as guided tours, coffee workshops, and tasting sessions emphasize the unique Arabica Limow Lestari coffee, cultivated by KTH Silih Asih, a local community group. Effective marketing through digital platforms, partnerships, and influencer collaborations is vital for attracting visitors. This program diversifies farmers’ incomes, preserves cultural traditions, and drives regional economic development. The Coffee Fun Trip offers a replicable model of sustainable tourism, merging education, entertainment, and community empowerment to benefit both visitors and local stakeholders.